Estimating short and long run time-of-use tariff elasticities for PEA's customer demand - Prow Choompradit; Marpaung, Charles O.P.; Weerakorn Ongsakul; Singh, Jai Govind; PEA; Asian Institute of Technology ducation Cooperation Project; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2012)
The thesis mainly aims to estimate electricity demand elasticities of PEA{u2019}s customers with respect to TOU tariffs in short- and long-run. The electricity demand for PEA{u2019}s clients is influenced by five variables, including peak prices, off-peak prices, amount of users, GDP and temperature. Along the study, double-log functional form is utilized through two notable approaches, partial adjustment and cointegration. GDP is found to be a major factor positively influencing upon electricity consumption among business sectors in both short-and long-run. On the contrary, residential sector shows highly demand sensitivity to temperature heightening with greater responsiveness in long run. The overall results show that all customer groups have inelastic demand responsiveness to one percent change in TOU tariffs. Besides, in the long run all the customers illustrate their greater concern to one percent rising in TOU prices, especially in peak periods. Peak and off-peak electricity are considered as substitutes. The main three types of PEA{u2019}s clients expose higher price sensitivity of their electricity demand, comprising of large-sized businesses, medium-sized businesses and small-sized businesses, respectively. Rarely changes in TOU prices might be a principal reason of inelastic tariff sensitivities among the customers. Consequently, policy makers should launch a more suited TOU tariffs based on diverse demand responsiveness in order to control probably an extremely excessive demand during peak period in the future.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Energy
Thesis (M.Sc.) - Asian Institute of Technology, 2012
Keywords: Electric power consumption -- Thailand